(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article analyzes specific using of gustatory lexical units as the means of representing rich national cuisine in the story “Culinary Figures” by M. Matios. This paper deals with several groups of lexical units that are widely used in the work such as: glutonic topos, instrumental units, nominative units. These gustatory words serve in the story “Culinary Figures” as the means of developing recipient’s imagination, stimulating appetite and contributing to the maximum visualization of national cuisine dishes. It also notes that Mariya Matios, before cooking the dish, recommends mistresses to do everything and start “thanks to their good graces”, since than the dish will be cooked in the delicious way. Descriptive stories perform the informative function and allow the reader to penetrate deeply into the world of national traditions. Among the different recipes of the dishes in the novel there are usual, traditional and ceremonial ways of preparing food, which have long-lasting and well-scripted receipts. The article also shows that the writer uses the gustatory vocabulary to describe the landscapes of her native area Hutsulshchyna. The main focus is put on the names of the following dishes: “Traces of innocence”, “Rose heart”, “Cabbage temptation”, “Dagger”, “Love hook”, the red borsch “The death of the rival”, “Meat stuff”, “The angel trace” “Curly Amour”, “Quiet heart”, stuffed cracknels “Who knows what», a salad “Greetings from America or swallow your fingers”. The writer compares cooking procedure with the process of divination. Each sentence of this work represents writer’s love for the traditions of folk cuisine, the ability to improvise during cooking, the feeling of love for culinary and gastronomic art, which carries out not only the functions of physiological satisfaction, but also aesthetic ones. In addition, it should be noted that in the “Culinary Figures” there are such gustatory terms as “delicious”, “sweet”, “rich”, “edible”, etc. Though these adjectives are actively functioning as relativistic, but this group of words can be reliably attributed to the category of adjectives, which denote both simple and complicated feelings of taste.